Transformasi Digital, Inovasi Terbuka, dan Pengambilan Keputusan Berbasis Data: Implikasi bagi Strategi Bisnis - Maulana, Arman (Koaliansi : Cooperative Journal, 2025)
Digital transformation has fundamentally changed the way companies create, deliver, and capture value. Developments in information technology, the Industrial Revolution 4.0, and changes in consumer behavior are driving a shift from conventional business models to more flexible, adaptive, and data-driven digital business models. This study uses a library research method, reviewing literature from national and international journals that discuss digital business models, network effects, digital marketing performance metrics, open innovation, and the integration of people, processes, technology, and data analytics within a data-driven decision-making framework. The study's findings indicate that both digital and conventional business models have their own strengths and challenges, but combining them can produce a more sustainable strategy. Network effects have proven to be a critical factor in the success or failure of startups, while selecting the right digital marketing metrics is crucial for the effectiveness of marketing strategies. Open innovation offers opportunities to accelerate innovation, although it still carries the risk of external collaboration. Ultimately, the integration of people, processes, technology, and data analytics has proven crucial in driving organizations to become more adaptive, innovative, and data-driven in the face of business uncertainty.Keywords: Digital transformation; Business model; Network effect; Open innovation; Data-driven decision-making.